Implementation of Tahfidz Al-Qur'an Ability Through the Qur'an Reading and Writing Program at SMA Negeri 2 Muara Beliti, Musi Rawas Regency - Alfiah; Khozin; Hakim, Rahmad (Zona Education Indonesia, 2025)
This research aims to analyze the Al-Qur'an memorization (tahfidz) ability, as well as to understand the efforts made by SMA Negeri 2 Muara Beliti in improving Al-Qur'an memorization ability through the Tuntas Baca Tulis Al-Qur'an (Complete Reading and Writing of the Al-Qur'an) Program. The informants were Al-Qur'an memorization teachers and tenth-grade students. Data collection employed observation, documentation, and interview techniques. Data triangulation was used to test the validity of the data. The research results indicate that: 1) The stronger the intention and motivation to memorize the Al-Qur'an, the greater the effort that will be made. 2) Each individual has a different memory capacity. Some find it easier to remember, while others require more time. 3) Concentration and the ability to focus on memorization without distractions will be very helpful. 4) Understanding the meaning of the verses being memorized can strengthen memory and make memorization more meaningful. 5) Linguistic and logical-mathematical intelligence can influence the speed of memorization. Consequently, based on the research results above, many students were able to complete the memorization of Juz 30 of the Al-Qur'an in less than 1 year